Gender Differences in the Adoption, Usage, and Perceived Effectiveness of AI Writing Tools: A Study Among University for Development Studies Students - Iddrisu, Hassan Mubarik; Iddrisu, Simon Alhassan; Aminu, Bashiru (International Journal of Educational Innovation and Research, 2025)
The purpose of this paper is to investigate gender differences in the adoption, use patterns and perceived effectiveness of AI writing tools by undergraduate students at the University for Development Studies (UDS). In light of the rapid adoption of AI tools into the landscape of higher education, it is important to examine male and female students as they relate to the usage and perceptions of AI in higher education. This study employs the Technology Acceptance Model (TAM) as a theoretical framework to explore how factors such as perceived ease of use, perceived usefulness, and attitudes toward technology influence AI adoption and usage patterns. A cross-sectional survey design was used for data collection using a structured questionnaire from 320 students across three departments. Statistical analyses (including t-tests and chi-square tests) were used to examine differences by gender. More than three-fourths (76.9%) of student respondents reported the use of AI tools, while 31.6% reported daily use. No significant differences were found between male and female students on perceived effectiveness, and both male and female students perceived AI tools as being effective. Results demonstrate the comorbid use of artificial intelligence in the academic writing context and imply that any gender differences in AI output are mitigated by the supportive capabilities of AI tools. The study's implications highlight the need for educators to provide equitable access and training in AI tools to support diverse student needs. Policymakers and developers should focus on designing inclusive AI writing tools that address potential barriers, ensuring all students benefit equally from technological advancements in education.